2012
DOI: 10.3324/haematol.2011.057620
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically aged red blood cells undergo erythrophagocytosis in vivo but not in vitro

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe lifespan of red blood cells is terminated when macrophages remove senescent red blood cells by erythrophagocytosis. This puts macrophages at the center of systemic iron recycling in addition to their functions in tissue remodeling and innate immunity. Thus far, erythrophagocytosis has been studied by evaluating phagocytosis of erythrocytes that were damaged to mimic senescence. These studies have demonstrated that acquisition of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 67 publications
2
92
0
2
Order By: Relevance
“…mice. 22,23 Gilson et al 24 as well as Hod et al 25 reported that after 14 days of storage in CPDA-1, murine RBCs had an in vivo 24-h RBC recovery of 64% to 65%, which is similar to the data from human RBCs stored for 42 days. 26 Yu et al reproduced the mature model, characterized the biochemical and functional effects, and studied the mechanisms responsible for the adverse effects of transfusing stored RBCs.…”
Section: Discussionsupporting
confidence: 76%
“…mice. 22,23 Gilson et al 24 as well as Hod et al 25 reported that after 14 days of storage in CPDA-1, murine RBCs had an in vivo 24-h RBC recovery of 64% to 65%, which is similar to the data from human RBCs stored for 42 days. 26 Yu et al reproduced the mature model, characterized the biochemical and functional effects, and studied the mechanisms responsible for the adverse effects of transfusing stored RBCs.…”
Section: Discussionsupporting
confidence: 76%
“…As such, exposure of phosphatidylserine (PS) may be a more important feature of eryptotic cells, compared with normally senescent RBCs. 3,12 Interestingly, an elevated [Ca 21 ] i has been found to be an important event in eryptosis induction in a majority of the cases, suggesting that this effector function could be one key mechanism behind eryptosis. 11,13 An increased [Ca 21 ] i is likely a consequence of Ca 21 entry through Ca 21 -permeable nonselective cation channels in the RBC membrane.…”
mentioning
confidence: 97%
“…Зміни поверхневих мембранних маркерів при старінні, гіпотермічному зберіганні та розвитку патофізіологічних процесів в еритроцитах, корелюють зі зниженням життєздатності та стабільності клітин [1,2]. Вочевидь, поверхневі характеристики віддзеркалюють структурно-функціональні перебудови мембран, які викликані різними стресовими факторами.…”
Section: вступunclassified